利用多个光源的计算机断层扫描装置及计算机断层扫描方法 (2025)
根据多样实施例的计算机断层扫描装置可以包括：扫描架，所述扫描架包括共享一个旋转轴并能够彼此独立旋转的环形态的第一旋转装置、第二旋转装置及第三旋转装置；多个第一光源，所述多个第一光源按一定间隔配置于所述第一旋转装置且以向对象体照射X射线的方式构成；多个第二光源，所述多个第二光源按一定间隔配置于所述第二旋转装置且以向对象体照射X射线的方式构成；检测装置，所述检测装置配置于所述第三旋转装置的一区域且以检测穿透所述对象体的X射线的方式构成；以及一个以上的处理器。 A computed tomography (CT) apparatus according to various embodiments may include a gantry including a first rotation device, a second rotation device and a third rotation device which have a ring shape, share an axis of rotation, and are rotatable independently of one another, a plurality of first light sources provided on the first rotation device at regular intervals and configured to emit X-rays to a subject, a plurality of second light sources provided on the second rotation device at regular intervals and configured to emit X-rays to the subject, a detector provided on a region of the third rotation device and configured to detect X-rays passing through the subject, and one or more processors.